2003
DOI: 10.1111/j.1745-9125.2003.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Victim Impact Panels on Dui Rearrest Rates: A Five‐year Follow‐up*

Abstract: Victim Impact Panels (VIPs) were introduced by Mothers Against Drunk Driving (MADD) in 1982 and have since spread throughout the United States in an attempt to reduce drunk driving. The objective of a VIP is to expose DUI offenders to the pain and suffering caused by drunk driving without necessarily condemning the DUI offender. The few scientific evaluations of the effectiveness of VIPs have produced mixed results. The present investigation draws on evidence from a quasi‐experimental design and a five‐year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…For female repeat offenders, those who were referred to VIP were significantly more likely to be re-arrested compared to those not referred, with an odds of re-arrest more than twice that of females who were not referred. three demonstrated a larger number of rearrests after VIP for those in the control group, compared to those in the VIP group (38,40,41), and one study found that VIP participants were more likely to be re-arrested than control group participants (42). Wheeler et al (37) investigated the effects of adding a VIP to the standard San Juan Country Driving While Impaired program in order to reduce re-arrest.…”
Section: Victim Impact Panels (Vip)mentioning
confidence: 99%
See 1 more Smart Citation
“…For female repeat offenders, those who were referred to VIP were significantly more likely to be re-arrested compared to those not referred, with an odds of re-arrest more than twice that of females who were not referred. three demonstrated a larger number of rearrests after VIP for those in the control group, compared to those in the VIP group (38,40,41), and one study found that VIP participants were more likely to be re-arrested than control group participants (42). Wheeler et al (37) investigated the effects of adding a VIP to the standard San Juan Country Driving While Impaired program in order to reduce re-arrest.…”
Section: Victim Impact Panels (Vip)mentioning
confidence: 99%
“…VIP have been considered to be quite expensive and require significant effort (36). Seven of the studies utilized an intervention comprising Victim Impact Panels (36)(37)(38)(39)(40)(41)(42). Three of these studies reported no differences between the intervention group and their respective control groups (36,37,39), Re-arrest VIP referral was not statistically associated with recidivism for female or male first offenders.…”
Section: Victim Impact Panels (Vip)mentioning
confidence: 99%
“…Purely educational programs have been found to be ineffective, and mixed results have been found for Victim Impact Panels (VIP) (Rojek et al, 2003;Wells-Parker, 2004). There is greater reduction in DUI recidivism when programs use a multi-component approach that combines AOD and driving education with treatment components (e.g., cognitive-behavioral therapy) (Nochajski and Stasiewicz, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…VIPs provide the victim an opportunity to confront his/her offenders by sharing the psychological, physical, and or financial impact of the offense on the victim; the duration of each session lasts about 20 min, and the offender is not allowed to speak until the victim has finished his/her story (Soper & Baessler, 2004). In addition to Soper and Baessler (2004), the Clark County VIP Study in Georgia also noted that participants in the program recommitted at lower rates (Rojek, Coverdill, & Fors, 2003). The study used a comparison group of first and repeat offenders and found that 33.5% of the comparison group repeated within a five-year period post-VIP (Rojek et al, 2003).…”
Section: Introductionmentioning
confidence: 94%